Can board diversity and choice of auditor enhance profitability? - Ferraz, D. P.; Lopes, I. T.; Kopliku, A. (International Journal of Business Performance Management, 2018)
The research examines how board diversity and choice of auditing firm, as mechanisms of corporate governance, affect the profitability of Iberian companies. Using information from an adjusted sample of 93 non-financial companies listed on the Iberian stock exchanges, a theoretical model was regressed. Profit margin (PM) and return on equity (ROE), as two of the more frequently used profitability measures, capture, at a moderately acceptable level, the impact derived from board diversity and choice of auditing firm among Iberian companies. Most variables cited are not equally distributed across Iberia, in line with Hofstede’s cultural dimensions model. The evidence, while inconclusive, provides valuable insight into how governance mechanisms affect performance. In addition, the research provides value to the literature by introducing new proxies on board characteristics, and its impact on dynamic profitability.